Women's participation in the political life of Kazakhstan: regulatory aspects - Serikzhanova, А.T.; Nurtazina, R.A. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
This article discusses legislative measures in Kazakhstan that encourage women's political participation as a crucial base for a successful democracy, highlights advancements and identifies challenges. Through thorough analysis, we have examined the legal and regulatory framework that governs women's political participation within our country's political landscape. This framework is designed to ensure equal rights and opportunities for both men and women, with the ultimate goal of eradicating gender-based discrimination. Comprehensive measures have been put in place to eliminate gender inequality within the political sphere, and equal opportunities and treatment are provided to girls and women. Our analysis takes into account both national and international laws. As we crafted the article, we conducted a thorough analysis of content and monitored internet resources. In doing so, we carefully considered the perspectives of experts on the subject of quotas for women, youth, and individuals with disabilities. These experts were divided into two groups, with some viewing quotas as discriminatory and others seeing them as a means to promote political rights for women. We have analyzed statistical data on the representation of women in various fields, such as science, secondary and vocational education, the judicial system, small and medium businesses, and decision-making bodies like the government, Majilis, Maslikhats, Akimats, Senate, and corporations.